A numerical study on condensation flow and heat transfer of refrigerant in minichannels of printed circuit heat exchanger. (June 2019) - Zhao, Zhongchao; Zhang, Yanrui; Chen, Xudong; Ma, Xiaolong; Yang, Shan; Li, Shilin
Highlights: The condensation flow of R22 in PCHE minichannels was investigated. The condensation patterns along the channel were analyzed and plotted to map. Effects of inlet quality on pressure drop and heat transfer were evaluated. Effects of R22 mass flux on pressure drop and heat transfer were assessed. The Nusselt number and Fanning factor correlations were proposed and verified. Abstract: Printed circuit heat exchanger (PCHE), with the core comprising many mini/microchannels, have been extensively studied, but few works involved two-phase flow. A simplified channel model of PCHE hot side was herein established to numerically explore the heat transfer and condensation flow performance of R22 in minichannels under different conditions. The model was a semicircular minichannel with 0.91 mm hydraulic diameter and 50 mm full length. The heat flux was kept at −77, 195 W m − 2, the inlet pressure was 0.63 MPa and the mass fluxes ranged from 58 to 93 kg m − 2 s − 1 . The condensation flow characteristics along the channel were analyzed. Four flow patterns, i.e., smooth-annular, wavy-annular, slug and bubbly, were noticed at different refrigerant mass fluxes and plotted as a flow pattern map. The effects of import vapor quality from 0.5 to 1 on pressure drop and heat transfer performance were evaluated. The heat transfer performance was optimal at the import vapor quality of 0.7. The impacts of refrigerant mass flux on pressure drop and local condensation heat transfer coefficient were assessed. Intermittent flow enhanced heat transfer. In addition, the correlations for local Nusselt number and Fanning friction factor were presented and compared with numerical data.